Diversitas Dewan Direksi dan Profitabilitas pada Perusahaan Terdaftar di Bursa Efek Indonesia - Yopie, Santi; Aw, Felicia (E-Jurnal Akuntansi, 2021)
The study discusses the problem of company performance by looking at the level of diversity of the board of education (gender, age, nationality and nationality), and the type of company. In this day and age, Diversity of workers and top management is one of the ways to increase productivity and work effectiveness of an organization. The study was conducted as a development of research that has applied hypothesis testing which is useful for testing how the influence of the independent variable on the dependent variable. The research was conducted on entities listed on the IDX from 2016-2020 (excluding entities in finance and insurance). The population is 514 entities. The number of samples used is 384 entities with purposive sampling method Data processing using statistical software SPSS and Eviews. The results of the study show that female directors, age and nationality have no significant effect on ROA, ROE and Tobin`s Q, while education has no significant effect on ROA, ROE, but has a significant negative effect on Tobin`s Q. Keywords: Profitability; Gender; Age; Education; Citizenship.